2005
DOI: 10.1002/nme.1248
|View full text |Cite
|
Sign up to set email alerts
|

Finite element matrices in congruent subdomains and their effective use for large-scale computations

Abstract: SUMMARYThe structure of finite element matrices in congruent subdomains is studied. When a domain has a form of symmetries and/or periodicities, it is decomposed into a union of congruent subdomains, each of which is an image of a reference subdomain by an affine transformation with an orthogonal matrix whose components consist of −1, 0, and 1. Stiffness matrices in subdomains are expressed by one in the reference subdomain with renumbering indices and changing signs corresponding to the orthogonal matrices. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We have performed numerical experiments and found that the plume number increases from 4 to 12 when the viscosity ratio increases from 10 3 to 10 4 under some condition. The detail of the numerical results will be presented in a forthcoming paper [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have performed numerical experiments and found that the plume number increases from 4 to 12 when the viscosity ratio increases from 10 3 to 10 4 under some condition. The detail of the numerical results will be presented in a forthcoming paper [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…We can show that those equations are uniquely solvable. Once θ n h is given, (u n h , p n h ) is obtained from (9) and (10). Substituting θ n h and u n h to (11), θ n+1 h is solved.…”
Section: Remarkmentioning
confidence: 99%
“…Tabarraei and Sukumar [11] demonstrated that, for the special case of quadtree meshes, for the Poisson equation and for the elasticity problem, the stiffness matrix of a subelement is the same as the stiffness matrix of the parent. Suzuki and Tabata [20] also showed the importance of reusing previous calculations studying the structure of the finite element mass and stiffness matrices of congruent subdomains (each of them being an image of a reference subdomain by an affine transformation, see [20] for further details). As a result, Suzuki and Tabata were able to express the global matrices as functions of the submatrices in the reference subdomain.…”
Section: Hierarchical Properties Between Geometrically Similar Elementsmentioning
confidence: 99%
“…elstct1 was used in [18]. Matrices stokes1 and stokes2 are obtained from a P 1-P 1 stabilized finite element discretization of the Stokes equations in a three-dimensional domain [36]. The matrix stokes1 is set with stress free boundary conditions, and then it has the six dimensional kernel corresponding to all rigid body modes of velocity and stokes2 with Dirichlet boundary conditions, the one dimensional kernel to a pressure lifting.…”
Section: Advantage Of Task Scheduling With Asynchronous Executionmentioning
confidence: 99%